GESTATIONAL TOXOPLASMOSIS: NARRATIVE REVIEW - Espitia De La Hoz, Franklin José (2024)
Gestational toxoplasmosis is a parasitic infection of major public health relevance due to its potential for maternal–fetal transmission and its impact on fetal and neonatal outcomes. This review aimed to analyze the diagnostic, therapeutic, and preventive approach to Toxoplasma gondii infection during pregnancy. A review of scientific literature published between 1973 and 2023 was conducted, including clinical trials, meta-analyses, observational studies, and management guidelines in English and Spanish. The evidence indicates that timely diagnosis requires the combined interpretation of serological tests, mainly IgG, IgM, and IgA antibodies, complemented by IgG avidity testing to distinguish recent from past infection. In cases of suspected fetal infection, polymerase chain reaction testing of amniotic fluid, performed after 18 weeks of gestation, represents a key diagnostic tool. Prenatal treatment with spiramycin may reduce vertical transmission, particularly when initiated early, whereas regimens including pyrimethamine, sulfadiazine, and folinic acid are reserved for confirmed or highly suspected fetal infection. Prevention through prenatal screening, hygienic-dietary counseling, and adequate obstetric follow-up is essential to reduce associated morbidity and mortality. In conclusion, gestational toxoplasmosis requires an early, comprehensive, and protocol-based approach to prevent congenital complications and improve maternal–fetal outcomes.